Collaborative practice in health education: Experience report of PET health Interprofessionality (Research, Society and Development, 2021)
Objective: To report the experience of a tutorial learning group from PET Health Interprofessionality, with a view to promoting collaborative practice in health education. Method: This is an experience report of a tutorial learning group from the PET Health Interprofessionality project in a municipality in the state of Pernambuco. The team includes teaching tutors, professional from the service preceptor and undergraduate and residency students, covering the following courses: physical education, nursing, nutrition, psychology, public health and social work. Weekly meetings are held for theoretical study, preparation of educational material and discussion of complex cases, as well as home visits to families being monitored. Results: In 2020, families with major problems of obesity and psychological distress were systematically monitored. Each week, home visits were carried out by a subgroup of tutors and students, to assess and intervene with families. The cases were discussed at the meetings, in which joint intervention proposals were prepared, through collaborative practice. Conclusion: It was observed that the project promoted the integration of teaching-service-community, provided students with the experience of collaborative interprofessional practice in their training, as well as individualized and quality care to assisted families.